An improved path splitting strategy on successive cancellation list decoder for polar codes. Issue 9 (9th March 2021) - Peng, Yunlong; Bao, Jingyun; Liu, Xingcheng
Abstract: The performance of the cyclic redundancy check aided successive cancellation list (CA‐SCL) decoder for polar codes exceeds that of the Turbo codes and the Low Density Parity Check (LDPC) codes adopted in the World Interoperability for Microwave Access (WiMAX) proposal. However, CA‐SCL decoder has a high computational complexity, resulting in a long time delay and high memory complexity. In order to alleviate this problem, an improved path splitting strategy on successive cancellation list (IPSS‐SCL) decoder was proposed, which can significantly reduce the average list size. The influence of splitting on CA‐SCL decoder was analysed at first and a new selective splitting criterion using the Gaussian approximation method was proposed according to the analysis. In addition, a path contraction mechanism based on the location estimation of the correct path was proposed to further reduce the average number of unnecessary candidate paths. Compared with existing path splitting strategies, simulation results show that the proposed IPSS‐SCL decoding algorithm can reduce the average computational complexity significantly over the additive white Gaussian noise (AWGN) channel with almost no performance loss.